Sustainable Education and Degrowth: International Trends - Kılıç, Gülenay Nagihan; Kocabaş, İbrahim (Springer, 2025)
In the twenty-first century, sustainability has become a critical concept in addressing economic, social, and environmental challenges. Within this context, education plays a pivotal role in raising awareness and fostering action toward a more sustainable future. However, mainstream approaches to sustainabilty have been criticized for perpetuating economic growth paradigms, prompting the need for alternative perspectives. Degrowth, an emerging concept, seeks to redefine sustainability by prioritizing ecological responsibility, social justice, and equity. This study employs a bibliometric analysis of publications indexed in the Web of Science (WoS) database between 2012 and 2025 to examine how sustainability and degrowth intersect within the academic discourse. The findings reveal dominant trends, thematic evolutions, and research gaps in the literature, highlighting the necessity of interdisciplinary approaches to align educational policies with degrowth principles. Moreover, this study underscores the importance of embedding degrowth-oriented values into educational practices to promote a more equitable and ecologically conscious future.
Keywords: Sustainability; Education; Degrowth; Bibliometric Analysis; Educational Policy